Team Building as a Tool to Strengthen the Company’s Position in the Market - Aleksandrovna Saenko, Lyudmila; Ivanovna Barsukova, Tatiana; Vasilyevna Khokhlova, Elena; Anatolyevna Ivashova, Valentina; Sergeevna Kenina, Diana (International Journal of Engineering and Technology, 2018)
The article considers the concept of team, team roles according to M. Belbin, factors affecting team building, team building model aimed at improving the quality of professional training ofÂ higher school graduates . Also, an analysis of the research of Russian scientists, the content analysis of the search service "Yandex" on request was conducted: team formation, team building tools, team building scenarios, grouping of factors affecting the process of team building. Official statistics, official fertility rates and the liquidation rate of enterprises in the Russian Federation were analyzed. The interaction between the model of organizational behavior and the model of teambuilding is considered. An effective model of teambuilding in educational organizations was developed, which allows developing such qualities among students as: stress-resistance, sociability, creativity, ability to work in a team. Â